Online banking. - Stewart, Kate (International journal of bank marketing, 2003)
This is the second of two issues of the journaldedicated to online banking issues. The firstissue concentrated on European papers. Thisissue contains papers from India, the USA, Singapore and New Zealand. The paper by Mukherjee and Nath reportsfindings from a survey of over 500 onlinebank customers in Calcutta.